Prevalence, severity, duration and resolution of cholestasis after acute liver failure - Marie Sinclair; Rinaldo Bellomo; Adam Testro; Ary Serpa Neto; Paul Gow; Stephen Warrillow; Scott Warming; Claire Michel; Kartik Kishore; Nada Marhoon; Natasha Holmes (BMJ Open Gastroenterology)
Objective Persistent cholestasis may follow acute liver failure (ALF), but its course remains unknown. We aimed to describe the prevalence, onset, severity, duration and resolution of post-ALF cholestasis.Design Cohort of 127 adult patients with ALF at a liver transplantation centre identified using electronic databases. We obtained laboratory data every 6 hours for the first week, daily until day 30 and weekly, when documented, until day 180.Results Median age was 40.7 (IQR 31.0–52.4) years, median peak alanine aminotransferase level was 5494 (2521–8819) U/L and 87 (68.5%) cases had paracetamol toxicity. Overall, 12.6% underwent transplantation (3.4% for paracetamol vs 32.5% for non-paracetamol; p<0.001). Ninety-day mortality was 20.7% for paracetamol versus 30.0% for non-paracetamol patients. All non-transplanted survivors reached a bilirubin level>50 µmol/L, which peaked 3.5 (1.0–10.1) days after admission at 169.0 (80.0–302.0) µmol/L. At hospital discharge, 18.8% of patients had normal bilirubin levels and, at a median follow-up time from admission to last measurement of 16 (10-30) days, 46.9% had normal levels. Similarly, there was an increase in alkaline phosphatase (ALP) (207.0 (148.0–292.5) U/L) and gamma-glutamyl transferase (GGT) (336.0 (209.5–554.5) U/L) peaking at 4.5 days, with normalised values in 40.3% and 8.3% at hospital discharge.Conclusion Post-ALF cholestasis is ubiquitous. Bilirubin, ALP and GGT peak at 3 to 5 days and, return to baseline in the minority of patients at median follow-up of 16 days. These data inform clinical expectations of the natural course of this condition.